2022
DOI: 10.1155/2022/8347125
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals the Role of Epithelial Cell Marker Genes in Predicting the Prognosis of Colorectal Cancer Patients

Abstract: Single-cell RNA sequencing (scRNA-seq) is increasingly used in studies on gastrointestinal cancers. This study investigated the prognostic value of epithelial cell-associated biomarkers in colorectal cancer (CRC) using scRNA-seq data. We downloaded and analysed scRNA-seq data from four CRC samples from the Gene Expression Omnibus (GEO), and we identified marker genes of malignant epithelial cells (MECs) using CRC transcriptome and clinical data downloaded from The Cancer Genome Atlas (TCGA) and GEO as training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Through the pathway enrichment analysis, we found that the antigen-presenting function of GCB in tumors was significantly increased, favourably supporting the activation and proliferation of T cells, and at the same time, it was also carrying out effective VDJ rearrangement to improve the affinity of specific antigens, with positive anti-tumor effects. In the down-regulated pathway, we also found that the pathway related to the secretion of antibodies was significantly down-regulated, suggesting that one of the reasons for the decrease of plasma cells may be caused by the decreased trend of GCB transformation[ 31 - 33 ]. In order to further explore the influence of microenvironment GCB cells on their own function, we found through the analysis of cell interaction molecular pairs that the molecular pairs that inhibit T cell function decreased significantly, while the molecular pairs that promote the activation and development of T cells and B cells were also significantly up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Through the pathway enrichment analysis, we found that the antigen-presenting function of GCB in tumors was significantly increased, favourably supporting the activation and proliferation of T cells, and at the same time, it was also carrying out effective VDJ rearrangement to improve the affinity of specific antigens, with positive anti-tumor effects. In the down-regulated pathway, we also found that the pathway related to the secretion of antibodies was significantly down-regulated, suggesting that one of the reasons for the decrease of plasma cells may be caused by the decreased trend of GCB transformation[ 31 - 33 ]. In order to further explore the influence of microenvironment GCB cells on their own function, we found through the analysis of cell interaction molecular pairs that the molecular pairs that inhibit T cell function decreased significantly, while the molecular pairs that promote the activation and development of T cells and B cells were also significantly up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…By performing Cox regression analysis on these findings, the MECRG risk score was obtained, based on patients being divided into two groups low-risk and high-risk. They evaluated the performance of their model using signature geneset solely and in combination with clinical information, namely age and TNM stage [ 36 ] comparing to their result in using signature geneset alone, our model perform better on test datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, their study indicated that the overexpressed tyrosine kinases BMX or HCK could initiate adenoma formation and strongly facilitate the genesis of CRC, thereby adding to our understanding of the evolutionary progress of epithelial cells into CRC cells at a single-cell resolution [118]. Likewise, Shen et al utilized scRNAseq data from open databases to develop a predictive model for assessing the prognostic performance of CRC based on epithelial cell marker genes [119]. It could be concluded from these studies that SCS-based CRC-TIME analysis holds significant practical value in exploring CRC metastasis, intestinal metaplasia, and biomarker investigation.…”
Section: Other Applicationsmentioning
confidence: 99%